BRAZILIAN CULTURE AND POPULAR IDENTITY: BRIEF CONSIDERATIONS - Rost, Isis Diana (2024)
National consciousness is a recent phenomenon, considered to be a specifically modern worldview. At the beginning of the twentieth century, the discussion about “what it means to be Brazilian” is accentuated. Three moments consolidate this discussion: the “formation” of samba, between the years 1910-1920, bringing together dances and Iberian-African rhythms, the period do Estado Novo (1930-1945) establishing samba as a synonym for national identity, and Tropicália (1967-1968), pointing out other paths for MPB. To build this text, we used Vianna (1995) and Basualdo ( 2007).